The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physreva.93.023628
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic growth dynamics and composite defects in quenched immiscible binary condensates

Abstract: We study the sensitivity of coupled condensate formation dynamics on the history of initial stochastic domain formation in the context of instantaneously quenched elongated harmonically-trapped immiscible twocomponent atomic Bose gases. The spontaneous generation of defects in the fastest condensing component, and subsequent coarse-graining dynamics, can lead to a deep oscillating microtrap into which the other component condenses, thereby establishing a long-lived composite defect in the form of a dark-bright… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 76 publications
2
27
0
Order By: Relevance
“…The comparison of our experimental data with the full simulation in the preceding sections has shown that it is vital to appropriately include the initial gravitational sag between the two species. The role of trap sag has previously been theoretically investigated in [30,31], while the effect of temperature has been considered in [27,42,[48][49][50]. Figure 7 provides a more complete analysis of the effect of the sag on the COM position of the expanded partially condensed 39 K cloud.…”
Section: Effect Of the Gravitational Sagmentioning
confidence: 99%
“…The comparison of our experimental data with the full simulation in the preceding sections has shown that it is vital to appropriately include the initial gravitational sag between the two species. The role of trap sag has previously been theoretically investigated in [30,31], while the effect of temperature has been considered in [27,42,[48][49][50]. Figure 7 provides a more complete analysis of the effect of the sag on the COM position of the expanded partially condensed 39 K cloud.…”
Section: Effect Of the Gravitational Sagmentioning
confidence: 99%
“…Their phase separations were observed in spinor BECs of sodium in all hyperfine states of F=1 [13]. The advances in the experimental investigations with multi-component BECs have activated a large amount of theoretical descriptions applied to condensed mixtures having spatially segregated phases, by studying their properties related to static and dynamical stability [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…[60][61][62] and Refs. [41,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78], respectfully. Notably, the SPGPE has been able to quantitatively describe experimental results, such as in Refs.…”
Section: Classical Field Methodologymentioning
confidence: 96%